2009
DOI: 10.1093/ndt/gfp505
|View full text |Cite
|
Sign up to set email alerts
|

Expression of renin-angiotensin system signalling compounds in maternal protein-restricted rats: effect on renal sodium excretion and blood pressure

Abstract: The current data led us to hypothesize that foetal undernutrition could be associated with decreased kidney expression of AT(R) resulting in the inability of renal tubules to handle the hydro-electrolyte balance, consequently causing arterial hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
125
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(159 citation statements)
references
References 45 publications
27
125
1
6
Order By: Relevance
“…We also found in FR50% animals, a graded and significant increase in blood pressure from the sixth week of life while, in LP offspring, the enhanced blood pressure was observed beyond the 12th week of age. 11,12 The current study also has demonstrated a reduction of 35% in the nephron number, against a 27% reduction in the LP model. 12,22 There is evidence that insult such as maternal food restriction, alters the total number of nephrons and also causes late-onset hypertension.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…We also found in FR50% animals, a graded and significant increase in blood pressure from the sixth week of life while, in LP offspring, the enhanced blood pressure was observed beyond the 12th week of age. 11,12 The current study also has demonstrated a reduction of 35% in the nephron number, against a 27% reduction in the LP model. 12,22 There is evidence that insult such as maternal food restriction, alters the total number of nephrons and also causes late-onset hypertension.…”
Section: Discussionsupporting
confidence: 53%
“…11,12,23,35 We cannot rule out that the decreased renal AngII receptor expression in the FR50% progeny may be simply an adaptive downregulation response that limits the fetal renal growth and post-natal sodium transport.…”
Section: Discussionmentioning
confidence: 96%
“…Among others, maternal low-protein diet (20), 50% food restriction (21) and glucocorticoid exposure (22) are the focus of many studies because they reflect the situation of people who live in poverty. Both of them result in LBW leading the fetus to develop adult diseases, like diabetes, heart disease and hypertension.…”
Section: Maternal-fetal Environment and Adult Diseasementioning
confidence: 99%
“…Fractional proximal (FEP Na ) and post-proximal (FEPP Na ) sodium excretion was calculated as C Li /C Cr × 100 and C Na /C Li × 100, respectively. [15][16][17] Data obtained over time were analysed using appropriate ANOVA for repetitive measurements. Post hoc comparisons between selected means were performed by Bonferroni's contrast test when initial ANOVA indicated statistical differences between experimental groups.…”
Section: Data Presentation and Statistical Analysismentioning
confidence: 99%